1998
DOI: 10.1021/bi980864l
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Xylanase fromThermomyceslanuginosus:  High-Resolution X-ray Structure and Modeling Studies,

Abstract: The crystal structure of the thermostable xylanase from Thermomyces lanuginosus was determined by single-crystal X-ray diffraction. The protein crystallizes in space group P21, a = 40.96(4) A, b = 52. 57(5) A, c = 50.47 (5) A, beta = 100.43(5) degrees, Z = 2. Diffraction data were collected at room temperature for a resolution range of 25-1.55 A, and the structure was solved by molecular replacement with the coordinates of xylanase II from Trichoderma reesei as a search model and refined to a crystallographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 64 publications
2
131
0
2
Order By: Relevance
“…Experimentally determined protein structures were obtained from the Protein Data Bank (22), including the following: bovine serum albumin (PDB code 4f5s) (23), the catalytic domains of Acidothermus cellulolyticus endocellulase E1 (Cel5A, PDB code 1c0d) (24), T. reesei cellobiohydrolase I (Cel7A, PDB code 1cel) (25), the family 1 carbohydrate-binding module of T. reesei Cel7A (CBM1, PDB code 1cbh) (26), Thermomyces lanuginosus endo-1,4-␤-xylanase (XynA, PDB code 1yna) (27), T. reesei eno-1,4-␤-xylanase (XynII, PDB code 1enx) (28), and T. reesei acetyl xylan esterase (AxeI, PDB code 1qoz) (29).…”
Section: Methodsmentioning
confidence: 99%
“…Experimentally determined protein structures were obtained from the Protein Data Bank (22), including the following: bovine serum albumin (PDB code 4f5s) (23), the catalytic domains of Acidothermus cellulolyticus endocellulase E1 (Cel5A, PDB code 1c0d) (24), T. reesei cellobiohydrolase I (Cel7A, PDB code 1cel) (25), the family 1 carbohydrate-binding module of T. reesei Cel7A (CBM1, PDB code 1cbh) (26), Thermomyces lanuginosus endo-1,4-␤-xylanase (XynA, PDB code 1yna) (27), T. reesei eno-1,4-␤-xylanase (XynII, PDB code 1enx) (28), and T. reesei acetyl xylan esterase (AxeI, PDB code 1qoz) (29).…”
Section: Methodsmentioning
confidence: 99%
“…Native xylanase of a strain of H. lanuginosa (T. lanuginosus) (245) and recombinant xylanase of strain DSM 5826 (101) were reported to contain a disulfide bond but no free OSH group. The native xylanase of DSM 5826 contained only a single, catalytically important cysteine but no intramolecular disulfide bond (53).…”
Section: Xylanasementioning
confidence: 99%
“…Structures of covalently attached epoxyalkyl glycosides to the active site residues of XYNII are also available, but these include only one xylose residue (29). Modeling studies with a xyloheptaose in the active site of Thermomyces lanuginosus xylanase (XynA) identify residues involved in subsite Ϫ2 (26). Recently the structure of an inactive mutant of the Xyn11 from Bacillus agaradhaerens in complex with xylotriose has been obtained (17).…”
Section: Production and Structural Properties Of The Xylanase Vari-mentioning
confidence: 99%
“…5, structural alignment of the above xylanases with that of A. niger enzyme showed that four of the A. niger xylanase variants (Y10A, Y89A, Y164A, and W172A) have been mutated at positions corresponding to residues that have been involved in discrete subsites of other family 11 xylanases. Tyr 10 corresponds to Trp Xyn11 , all involved in stacking interaction with the xylose ring in substite Ϫ2 of these xylanases (13,16,17,22,26 XYNII , which are thought to determine subsites ϩ1 and ϩ2 of XYNI and XYNII enzyme, respectively (22). Moreover, the oxygen atom OH of residue Tyr 6 is in the same position as atom Glu…”
Section: Production and Structural Properties Of The Xylanase Vari-mentioning
confidence: 99%
See 1 more Smart Citation